Anti-tumour necrosis factor therapy in seronegative spondyloarthritis. - Catherine, S; Bowness, P (2005)
Over 50% of ankylosing spondylitis patients treated with anti-tumour necrosis factor show a 50% improvement Infliximab, etanercept (and probably adalimumab) are equally effective Stable responses are maintained for two years If treatment is discontinued, almost all patients relapse Retreatment is probably as effective as initial treatment Pre-test screening for tuberculosis is essential The overall risk to benefit ratio is favourable.